Lingua fracas. (Economist, 2017)
The article discusses the news broadcasted in Cameroon's State Television Channel (CRTV). The national football team, The Indomitable Lions have defeated Egypt to win the Africa cup of Nations trophy for the first time in 15 years, while a teenager from the country has won the Google coding challenge, which is an International programming competition. It also brings up scenarios which show that the country is still in trouble whether it is the placard protests or the internet shut down.